Intrinsic qualities that determine success in entrepreneurs in the state of Tlaxcala, Mexico (GEON Journal (Management, Organizations and Business), 2022)
Problematic: Entrepreneurship is a complicated action and of great value. It is undeniable that anyone can set up a business, but not all will achieve success, because we do not have all the qualities to do so, discovering them to replicate them, is a complex but possible challenge. Objectives: Know the most consistent qualitative variables that determine success among entrepreneurs in the state of Tlaxcala in Mexico, in order to go deeper into them and replicate them in other places. Materials and methods: Qualitative and quantitative information has been collected from 243 cases, from which descriptive statistical data has been extracted to make correlations, inferential statistical analysis and multiple correspondence, in order to generate useful regularities for this proposal. Results: 21 variables were obtained that are consistent in relation to the dependent variable success, in whose results the influence of 12 intrinsic or ontic qualities or variables were observed with greater consideration and which supports the theoretical statements of this proposal. Discussion: The intrinsic or ontic variables are the most important in relation to the distance of correspondence with the dependent variable success and with this, it is ratified that the theory that supports these variables is even more important than the economic resources for entrepreneurship. Conclusions: It is verified that the Economic Units will be dynamic from the decision and actions of owners who possess qualities that are intrinsic, in accordance with the economic literature consulted. Entrepreneurship will be successful from the selectivity of entrepreneurs, since not all will be able to achieve success and it is important to be aware of this, to motivate and encourage certain business skills. Contribution / originality: There are no similar studies in the state of Tlaxcala in Mexico or disaggregated data on the subject. A business study methodology has been consistently worked on, where cases are analyzed and this proposal is applicable at any latitude to suggest strategies in the training of entrepreneurs.
Keywords: L21 Business objectives of the firm; L26 Entrepreneurship; M13 New firms/Start-ups; M15 IT management; M31 Marketing; M54 Labour management; decision making; entrepreneur; leadership; management; motivation; social and economic development